Suppression of cigarette smoke induced MMP1 expression by selective serotonin re‐uptake inhibitors. Issue 7 (17th June 2021) - Adam, Gerber; Shiomi, Takayuki; Monica, Goldklang; Jarrod, Sonett; Vincent, Anguiano; Becky, Mercer; Tina, Zelonina; Jeanine, D'Armiento
ABSTRACT: Globally, COPD remains a major cause of disability and death. In the United States alone, it is estimated that approximately 14 million people suffer from the disease. Given the high disease burden and requirement for chronic, long‐term medical care associated with COPD, it is essential that new disease modifying agents are developed to complement the symptomatic therapeutics currently available. In the present report, we have identified a potentially novel therapeutic agent through the use of a high throughput screen based on the knowledge that cigarette smoke induces the proteolytic enzyme MMP1 leading to destruction of the lung in COPD. A construct utilizing the cigarette responsive promoter element of MMP‐1 was conjugated to a luciferase reporter and utilized in an in vitro assay to screen the NIH Molecular Libraries Small Molecule Repository to identify putative targets that suppressed luciferase expression in response to cigarette smoke extract (CSE). Selective serotonin reuptake inhibitors potently inhibited luciferase expression and were further validated. SSRI treatment suppressed MMP‐1 production in small airway epithelial cells exposed to (CSE) in vitro as well as in smoke exposed rabbits. In addition, SSRI treatment inhibited inflammatory cytokine production while rescuing cigarette smoke induced downregulation in vivo of the anti‐inflammatory lipid transporter ABCA1, previously shown by our laboratory to be lung protective. Importantly, SSRI treatment prevented lung destruction in smoke exposed rabbits as measured by morphometry. These studies support further investigation into SSRIs as a novel therapeutic for COPD may be warranted.